At the end of the line: on kairological history. (3rd January 2020) - Holmes, Brooke
Abstract: This essay examines, from a position within Classics, different angles on critiques of historicism and the turn to anachronism in History, Art History, Medieval Studies, and Queer Theory before proposing the idea of 'kairological history', on the model of the artist Paul Chan's 'kairological art'. On this analysis, 'kairological history' engages the critical and creative resources of anachronic thinking alongside tools of historicism (e.g. empiricism, successionism, periodization, alterity) in making choices about 'telling time'. These choices reflect a critical understanding of how temporality shapes the valuation of the past, particularly in relation to a 'classical' past; the negotiation of identity and difference between past and present; and the kinds of communities that history aims to support. The second half of the essay examines two instances of anachronism within the history of anatomy, one from Galen and one from the early twenty-first century. Both cases represent problems that historicism can correct. But the modality of correction, in itself, is anaemic and risks the very teleology that linear history is so often faulted for. The essay therefore explores what gets lost and what gets found when temporality is aligned with linearity, as well as non-linear modes of telling time.